The Teachers’ Need for Teaching Supervision under the Office of Chonburi Primary Educational Service Area 3 - Seethim, Natkrita (Interdisciplinary Academic and Research Journal, 2023)
The teacher's educational management process must encourage learners to develop naturally and to their full potential. Learning management, therefore, needs to be aligned with the aptitudes, interests, and development of the learners. Educational supervision, therefore, plays an important role in the development of educational management to achieve the goals and objectives of teachers and to provide quality education. The purposes of this research were (1) to study the teaching supervision needs of teachers. And (2) compare the level of teaching supervision needs of teachers classified by level of teaching, academic position, and education level. This study studied teachers under the Office of Chonburi Primary Educational Service Area 3. The sample consisted of 322 teachers. The statistics used for data analysis were percentage, frequency, mean, standard deviation, F-test, and t-test. The results showed that; (1) Teachers' need for teaching supervision overall was at a high level, when considering each aspect, it was found that all items were at a high level. (2) The result of a comparative analysis of the level of needs for teaching supervision of teachers classified according to the level of teaching, the overall difference was statistically significant at the .05 level, Classified according to the overall and individual academic positions were not different. Classified by the level of education was not different overall, but different aspects in terms of preparation and operation were statistically significant at the .05 level.